DEVELOPMENT OF PROJECT-BASED DIY PHOTOMETER GUIDEBOOK IN NIGHT SKY BRIGHTNESS MEASUREMENT - Puji Asmoro, Cahyo
Night sky brightness (NSB) measurement is one of the activities carried out to determine the quality of the night sky in a place, this value is very useful for observers of night sky objects. The more celestial objects from the brightest to the faintest stars, galaxies, nebulae and so on that can be seen indicate the quality of the night sky in that location is very good. There are many studies that show that night sky quality is related to light pollution and air pollution, both of which have adverse implications for ecosystem life. In addition, by measuring NSB, many things can be known, namely, twilight events, long nights and dawn events. To make NSB measurements, one of the techniques used is with a tool called a photometer, the limitations of specific photometer tools for NSB measurements in units of magnitude per square arc second (mag / sq arc second ~ mpsas) have been answered by the availability of an independent photometer that has been validated. The next problem is that there is still no guidebook for using a DIY photometer that can guide students in making KLM measurements. In an effort to provide the utilization of DIY photometers in learning activities related to photometry, a project-based photometer guidebook was made through the stages of validation by experts and field tests on respondents. From the process of these stages, the average validation percentage obtained from validators consisting of material and media experts is 86.9% with very valid criteria, while from the test results, the percentage of student respondents' questionnaires is obtained with details of 28.6% strongly agreeing, 52.7% agreeing, 12.6% undecided and the average results of problembased task observations of 84.6% with very high criteria. So that the guidebook developed is suitable for use as a guide to the use of photometers for various learning and research purposes.